Religious Tolerance in Minangkabau from a Psychological Perspective - Mai Tiza Husna; Widia Sri Ardias; Indah Andika Octavia (Al-Adyan: Journal of Religious Studies, 2022)
Religious intolerance in Minangkabau is an issue that is often discussed recently, as reported in print and online media. This research aims to explain the psychological dynamics of the emergence of intolerant behavior and the efforts that can be made to increase religious tolerance from a psychological point of view. This research is a qualitative research with literature study. The results showed that there are 3 processes that occur when a person will take an action or not, the first is affective (positive or negative feelings about a group), psychological (open-minded thought) and behavior (tolerant or intolerant behavior).Intoleransi beragama di Minangkabau merupakan isu yang sering diperbincangkan akhir-akhir ini seperti diberitakan di media cetak dan online. Tulisan ini bertujuan untuk menjelaskan dinamika psikologis munculnya perilaku intoleran dan upaya yang dapat dilakukan untuk meningkatkan toleransi beragama dari segi psikologis. Penelitian ini merupakan penelitian kualitatif dengan studi pustaka. Hasil penelitian ini menunjukkan bahwa ada 3 proses yang terjadi ketika seseorang akan melakukan suatu tindakan toleransi atau intoleransi, yang pertama adalah afektif (perasaan positif atau negatif tentang suatu kelompok), psikologis (pikiran terbuka) dan perilaku (perilaku toleran atau intoleran).